Impact of Corporate Governance and Ownership on Firm Performance in The Emerging Market Economy Of Sri Lanka - Balagobei, S.; Velnampy, T. (Research gate, 2023)
The purpose of the study is to examine the impact of corporate governance and ownership on firm performance of listed companies in the emerging market of Sri Lanka. This study is confined to listed companies using a sample of 104 companies in Sri Lanka with 728 firm-year observations during the period of 7 years from 2015 to 2021. The statistical techniques of Pearson’s correlation and panel data regression were used to analyse the association between corporate governance, ownershipand firm performance. The findings of this study reveal that board size produces a positive impact on firm performance of listed companies in Sri Lanka. As per the fixed effects model, board independence, CEO duality and board diversity, board activity, managerial ownership and institutional ownership have not shown any significant impact on firm performance of listed companies in Sri Lanka. Control variables, firm size and firm age have a negative impact whereas leverage has a positive impact on firm performance of listed firms in Sri Lanka. These findings have implications for managers, policymakers, researchers and investors in general and those in developing countries in particular.
Keywords: Corporate Governance; Firm Performance; Ownership; JEL Classification : G32